How do dinosaurs learn their colors? - Yolen, Jane.; Teague, Mark (New York, N.Y. : Blue Sky Press, 2006)
Illustrations and rhyming text show dinosaurs learning the names of all the colors of the rainbow.
Cover title.
On board pages.
Adult 420
Keywords: Color -- Juvenile fiction; Dinosaurs -- Juvenile fiction; Stories in rhyme